2014
DOI: 10.1590/1678-6889
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do transporte de péletes sobre sua qualidade

Abstract: A peletização é um processo mecânico, que tem como objetivo agregar as partículas dos alimentos por meio de compressão sob altas temperaturas (80 a 90ºC) e vapor (Nir, 1998), a fim de obter péletes com grau de durabilidade suficiente para suportar as condições de transporte e manuseio. Melhor desempenho em frangos de corte alimentados com rações peletizadas, como aumento do ganho de peso e melhora na conversão alimentar, foi encontrado por Meiners et al. (2001) Van der Poel, 1996). Existem dois meios de a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
1
5
0
2
Order By: Relevance
“…It should be mentioned that samples were only taken at the pellet die unlike the current experiment where samples were taken at 4 points within the mill. Similar to our findings, Cardeal et al (2014) described an increase in PDI after the pellet die, which is most likely a result of the cooling process removing moisture from the pellet. Alternatively, the increase in PDI after the pellet die may be due to the poorest quality pellets being degraded early in the manufacturing process, leaving only the hardest and most durable pellets as they move through the Eight to 10 samples were taken from each location in the mill within a run for 8 runs over 3 weeks.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It should be mentioned that samples were only taken at the pellet die unlike the current experiment where samples were taken at 4 points within the mill. Similar to our findings, Cardeal et al (2014) described an increase in PDI after the pellet die, which is most likely a result of the cooling process removing moisture from the pellet. Alternatively, the increase in PDI after the pellet die may be due to the poorest quality pellets being degraded early in the manufacturing process, leaving only the hardest and most durable pellets as they move through the Eight to 10 samples were taken from each location in the mill within a run for 8 runs over 3 weeks.…”
Section: Resultssupporting
confidence: 91%
“…feed mill. In a notable difference from our experimental design, Cardeal et al (2014) observed that using a larger discharge opening on the feed truck auger resulted in an improved percentage of intact pellets, potentially because there was less friction within the auger, allowing pellets to maintain their structural integrity compared to pellets discharged using the smaller auger.…”
Section: Table 3 Nutrient Composition Of Fines and Pellets Collectedmentioning
confidence: 68%
See 1 more Smart Citation
“…The metodology criated by Schmidt et al (2004) for evaluate pellets quality by of MEP showed an aplication different in compared official method (PDI). According to Cardeal et al (2014) the PDI value does not show the real situation regarding the relationship between whole pellets and thin offered to animals as feed on the farm, which is demonstrated by MEP. Therefore, the PDI is a good method to evaluate pellet resistance in the feed mill, because there is high correlation with the MEP, which proved to be best method to evaluate the condition of the pellet in the field.…”
Section: Discussionmentioning
confidence: 96%
“…Pelletization is a mechanical process that combines food particles using high temperature (80 -90 °C) and steam, with the objective to form pellets resilient to transportation and handling (Cardeal et al, 2014), leading to low amounts of fine particles (Amerah et al, 2007), related to feed fragmentation and abrasion resis-Samples of pelleted feed were collected at different points, from the pelletizer dryer up to the end of the feeding line (100 m) and made of corn, soybean meal, degummed soybean oil, dicalcium phosphate, calcitic limestone in addition to vitamin and mineral premixes. The samples were collected on two different days and at two different farms of 100 x 12 m poultry houses equipped with automatic pan type feeders of the same brand, with the feed being distributed by a helical system coupled to a metal tube of 7.5 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%